SUBHASH CHANDRA BOSE : The Springing Tiger - Toye, Hugh, author 640854 (Mumbai : Jaico Publishing House, 2010)
Hugh Toye’s study of Subhash Chandra Bose is valuable on three counts: as a history of a little known facet of World War II, as a study in AngloIndian relations over a vital period, and as a study of the new kind of leaders in Asia. The story of Bose’s life is of absorbing interest, and the author makes him live in all his idealism, fiery nationalism, political astuteness and overriding arrogance. But more important are its implications, which must make the reader seriously rethink the role of EuropeanAsian relations and, in rethinking, arrive at a better understanding of what is happening now and what may happen.